1999
DOI: 10.1677/erc.0.0060187
|View full text |Cite
|
Sign up to set email alerts
|

Biology of aromatase inhibitors: pharmacology/endocrinology within the breast.

Abstract: Both mammary adipose tissue and breast cancers have the ability to aromatize androgens into oestrogens. Such potential may maintain the growth of hormone-dependent tumours. It has therefore been important to determine the effects of new aromatase inhibitors such as formestane, exemestane, anastrozole and letrozole on oestrogen biosynthesis and concentrations of endogenous hormones within the breast. Studies based on in vitro incubations of breast cancer and cultures of mammary adipose tissue fibroblasts demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(48 citation statements)
references
References 24 publications
0
46
0
2
Order By: Relevance
“…Groups 2 and 4 received a subcutaneous injection of 4-OHA (4-androsten-4-ol-3, 17-dione; Steraloids, Newport, RI) dissolved in corn oil (5 mg/kg body wt) just before resuscitation. The dosage regime of 4-OHA employed was based on previous in vitro studies, the treatment regime for patients with prostatic and breast cancer, and previous work by our laboratory (17,32,46). No deleterious side effects of subcutaneous 4-OHA administrations at this dose were observed in the present study.…”
mentioning
confidence: 88%
“…Groups 2 and 4 received a subcutaneous injection of 4-OHA (4-androsten-4-ol-3, 17-dione; Steraloids, Newport, RI) dissolved in corn oil (5 mg/kg body wt) just before resuscitation. The dosage regime of 4-OHA employed was based on previous in vitro studies, the treatment regime for patients with prostatic and breast cancer, and previous work by our laboratory (17,32,46). No deleterious side effects of subcutaneous 4-OHA administrations at this dose were observed in the present study.…”
mentioning
confidence: 88%
“…2). The concentration of anastrozole selected was based on studies by other investigators who demonstrated significant aromatase inhibition in vitro at this concentration (18). Anastrozole was added 60 min before the addition of testosterone.…”
Section: Effect Of Various Concentrations Of Testosterone and Dihydromentioning
confidence: 99%
“…In postmenopausal women, Arimidex, at a daily dose of 1 mg, produced estradiol suppression of greater than 80%. Arimidex does not possess progestogenic, androgenic, or estrogenic activity [14][15][16].…”
Section: Nolvadex ® (Tamoxifen Citrate)mentioning
confidence: 99%